2015
DOI: 10.11648/j.aff.20150406.20
|View full text |Cite
|
Sign up to set email alerts
|

Study on Present Status of Fish Biodiversity in Wetlands of Sylhet District, Bangladesh

Abstract: The study was conducted to identify the present status of fish biodiversity in the wetlands of Sylhet district for a period of 12 months from January 2014 to December 2014. It was done by questionnaire interviews (QI) of fishers, focus group discussions (FGD), and key informant interviews (KII) and secondary data collection. During the study period, a total of 58 fish species under 21 families were recorded. The species availability status was remarked in four categories and obtained as 24 commonly available, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…found a total of 63 fish species in the river of Choto Jamuna at Naogaon district, Bangladesh. Islam et al (2015c) recorded 61 species of fishes from the Sibsa River at southwestern part of Bangladesh. Thus, the species diversity of the Juri River is much higher than those rivers.…”
Section: Ichthyofaunal Diversity Statusmentioning
confidence: 99%
“…found a total of 63 fish species in the river of Choto Jamuna at Naogaon district, Bangladesh. Islam et al (2015c) recorded 61 species of fishes from the Sibsa River at southwestern part of Bangladesh. Thus, the species diversity of the Juri River is much higher than those rivers.…”
Section: Ichthyofaunal Diversity Statusmentioning
confidence: 99%
“…Similar to our results, Chowdhury et al [ 28 ] categorized 24, 19, 24, 7, and 3 fish species as available, moderately available, rarely available, very rarely available, and extinct, respectively among the 77 fish species under 25 families. Another study in Bangladesh reported that the highest number of fish species was observed from October to December; however, the lowest number of fish species was observed from March to April [ 29 ]. According to Islam et al [ 29 ], out of 54 threatened red-listed fish species by IUCN in Bangladesh, only 30 species were highly visible for the last 20 years, but, currently, 23 species were categorized as only visible.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Bangladesh reported that the highest number of fish species was observed from October to December; however, the lowest number of fish species was observed from March to April [ 29 ]. According to Islam et al [ 29 ], out of 54 threatened red-listed fish species by IUCN in Bangladesh, only 30 species were highly visible for the last 20 years, but, currently, 23 species were categorized as only visible. Subsequently, a large number of fish species were added to the red list by the IUCN Red List of Bangladesh [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rita rita is a commercially exploited fish species in Bangladesh and is appreciated for its high nutritious value (Mohanty et al, 2015). The natural distribution of this fish species is described from shallow and muddy to clear waters in rivers and wetlands of Bangladesh (Islam et al, 2015;Galib et al, 2016;Sultana et al, 2017;Jewel et al, 2018;Parvez et al, 2019) and in the closer countries (Gupta, 2015;Iqbal et al, 2017b;Muhammad et al, 2019). Nowadays, the populations of R. rita in the riverine ecosystem of Bangladesh are facing the critical threat of extinction due to over-exploitation and loss of breeding grounds (Molla et al, 2008).…”
Section: Introductionmentioning
confidence: 99%